2018
DOI: 10.1186/s12944-018-0688-6
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of black tea based flavonoids against hyperlipidemia related disorders

Abstract: BackgroundIn recent decade, Hyperlipidemia related disorders like obesity, hypercholesterolemia and diabetes are considered as the leading killers for mankind. Fundamental nexus between nutrition and health diverting the consumers focus towards plant based natural products as a remedy against various metabolic syndrome. Considering this, present study was conducted to explicate the role of black tea polyphenols such as Theaflavins and thearubigins therapeutic potential to tackle targeted maladies especially ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…Our study showed pro-hyperglycemic effects by BTE as indicated by increased levels of fasted and fed glucose as well as lesser glucose tolerance, whereas levels of insulin were not changed significantly. This is in contrast to previous animal studies, where a decline in glucose as well as an increase in insulin sensitivity and glucose tolerance were demonstrated by the treatment with black tea extracts or theaflavins (Anderson and Polansky, 2002;Imran et al, 2018;Miyata et al, 2013;Ramadan et al, 2009). However, a double-blind randomized study with T2D patients showed no effects on HbA1c (Mackenzie et al, 2007) which reflect our observation where no changes of HbA1c were measured in the BTE group (data not shown).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Our study showed pro-hyperglycemic effects by BTE as indicated by increased levels of fasted and fed glucose as well as lesser glucose tolerance, whereas levels of insulin were not changed significantly. This is in contrast to previous animal studies, where a decline in glucose as well as an increase in insulin sensitivity and glucose tolerance were demonstrated by the treatment with black tea extracts or theaflavins (Anderson and Polansky, 2002;Imran et al, 2018;Miyata et al, 2013;Ramadan et al, 2009). However, a double-blind randomized study with T2D patients showed no effects on HbA1c (Mackenzie et al, 2007) which reflect our observation where no changes of HbA1c were measured in the BTE group (data not shown).…”
Section: Discussioncontrasting
confidence: 92%
“…In our study, BTE treatment also caused a reduction of weight gain which corresponded to a significant decline in levels of triglycerides and LDL, paralleled by an increase in FFAs. In previous studies, positive effects against dyslipidemia by BTE had been demonstrated by a decrease in cholesterol, LDL and triglycerides and/or increase in HDL or theaflavins (Imran et al, 2018;Mahmoud et al, 2016;Miyata et al, 2013;Naveed et al, 2018;Ramadan et al, 2009). Metformin is a widely used T2D drug which significantly decreased fasted blood glucose levels in ZDF rats and improved glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG is one of the most abundant catechins in green tea (59% of total catechin) (Leung et al, 2001), and has potential health benefits in cancer treatments, autoimmune regulation and metabolic disease therapy (Legeay et al, 2015, Rawangkan et al, 2018. Theaflavins are found predominantly in black tea (Leung et al, 2001) and are thought to have neuroprotective, anti-inflammatory (Anandhan et al, 2013) and anti-hyperlipidaemia effects (Imran et al, 2018). In D. discoideum (Fig.…”
Section: Finding the Function Of Flavonoidsmentioning
confidence: 99%
“…This versatility had encouraged the supplementation of phytochemicals to modulate the onset of chronic ailments such as cancer and other metabolic syndromes (Gülçin, ; Taslimi & Gulçin, ). Theaflavins (TF) and thearubigins (TR) have been investigated against obesity, diabetes, and renal failure and found effective against these ailments owing to their antioxidant potential (Imran, Arshad et al, ; Imran, Butt et al, ).…”
Section: Introductionmentioning
confidence: 99%